Fame and infamy in Roman sexuality - Cavicchioli, Marina Regis (Romanitas - Revista de Estudos Grecolatinos, 2014)
Several sexual acts are associated to moral and symbolic values able to assign to who practice them a good or bad fame. In the Roman world of the first century the sexuality ​​tied to, among other things, issue of citizenship and manhood. The iconography, epigraphy and a few poems appear as a beautiful illustration of how a particular sexual morality was founded. It is also true that these elements allow us the understanding of sexual morality associated to values whose attribution belongs to social groups, in other words, that there wouldn’t be a single sexual morality whose validity was independent of the particular values ​​of each sector of society. So, a certain behavior that characterizes fame of the point of view of a group, could mean infamy to another. In this sense, it is necessary to analyze iconographic, epigraphic and poetic elements with the purpose of demonstrating in what extent were related to fame and infamy concerning to sexuality.
Keywords: Material Culture; Pompeii; Fame; Infamy; Sexuality